Políticas de ingresso na educação superior pública: modalidades de concorrência nos processos seletivos da UFT - Uma proposta de plataforma orientativa - Borba, Deusmar Oliveira de (Universidade Federal do Tocantins, 2024)
It discusses the historical context of the forms of access to Brazilian public universities, until we get to the selection processes for students to enter the Federal University of Tocantins- UFT, Arraias Campus, where the research is applicable. The problem of this study was mobilized, initially, by the researcher's role as academic secretary on the campus of Arraias. Where we can verify some difficulties encountered when enrolling in the different competition modalities of the selection processes offered by UFT, as well as some recurrent problems they face in enrolling when summoned. The justification for this research is relevant insofar as it discusses the different forms of entry that UFT offers to candidates when they apply for one of the vacancies offered by the institution and are faced with different types of competition within the selection processes. This study is also justified in order to help candidates in the UFT/Arraias competitions that precede the selection and also after, still in the preliminary phase, as it is a time to interpret and understand the selection notices that end up bringing various information that is not are known and familiar to the candidates, thus generating doubts about which way to go and whether their real situation fits the criteria defined in the public notice. With this study, it is also intended to facilitate the analysis of the public notices, by the candidates, and to help them in the decision-making about the modality in which they intend to compete in the different selective processes of the UFT, presenting the proposal of development of a product that has a language closer to the students, making the information available in the notices more accessible. Methodologically, the research is characterized as qualitative and quantitative, of an applied nature, of a bibliographical nature, as it was developed based on already elaborated sources, from theoretical references published in electronic and printed media, seeking to deepen the information and produce new knowledge. Finally bringing a proposal for an interactive environment, where information about the selection processes of UFT can be demonstrated, highlighting the available competition modalities and what are the criteria to compete in a certain modality.